EVALUASI KANDUNGAN KLORIDA (CL-) dan DAYA HANTAR LISTRIK (DHL) AIR TANAH PADA SISTEM AKUIFER JAKARTA PERIODA 1990-2000 - Indriatmoko, Robertus Haryoto; J, E. Myra. (Center for Environmental Technology, 2005)
Evaluation of chloride (Cl-) content and electric conductivityÃ‚Â (EC) of ground water in aquifer system is one method to identify salt water movement in aquifer system, which occurred as a result of changes in hydraulic equilibrium which cause by temporary variation of natural recharges and pumping of ground water at many layered aquifers.Salt water movement in Jakarta aquifer system is evaluated based on mapping of chloride content at 500 mg/L and EC at 1500 m mhos/cm in many bored well during period of 1990 Ã¢â‚¬â€œ 2000. In the beginning chloride content and EC is in value only and with the addition of attribute data, namely coordinate, it could be used as input data. By using software namely SURF, the above input data is simulate to have a contour map of chloride and EC. Overlapping of the contour map to Jakarta base map will result in thematic map of chloride and EC distribution which represent salt water movement at Jakarta aquifer system.Ã‚Â Ã‚Â Key word : Aquifers, Aquifer system, Chloride (Cl-) , Electric Conductivity (EC), Map, Hydraulic Equilibrium, Ground water, SURF Software.